Does Migration Theory Explain International Migration From Bangladesh? A Primer Review - Wadood, Syed Naimul; Choudhury, Nayeema Nusrat; Azad, Abul Kalam (Social Science Review, 2023)
This is a primer review of international migration theory and international migration from Bangladesh. We first present a review of the theory of international migration. Regarding international migration from Bangladesh, we note that by the middle of 2020, about 7.4 million people of Bangladesh origin were staying overseas, the sixth-largest worldwide and second-largest in South Asia. Yet there are concerns about illegal human trafficking and smuggling of undocumented workers. Recently there has been the COVID-19 pandemic, starting from the end of 2019 to date. Bangladesh international migration ground realities are often uncertain and challenging, with new situations emerging now and then in many different host countries. In summary, we argue that recent models of migration theory (circular, onward and return migration models) have successfully incorporated issues of international migration from large source countries, such as Bangladesh. Social Science Review, Vol. 38(2), December 2021 Page 51-69